2022
DOI: 10.3389/fonc.2022.879399
|View full text |Cite
|
Sign up to set email alerts
|

Could We Safely Avoid a Second Resection in Selected Patients With T1 Non-Muscle-Invasive Bladder Cancer? Preliminary Results of Cost-Effectiveness Study From HUmanitas New Indications for ReTUR (HuNIRe) Multicenter Prospective Trial

Abstract: ObjectivesThe aim of this study is to assess whether restaging transurethral resection (ReTUR) could be safely replaced with urine cytology (UC) and in-office fiexible cystoscopy in selected T1 non-muscle-invasive bladder cancer (NMIBC).Materials and MethodsThis is an ongoing prospective multicenter trial enrolling patients diagnosed with T1 BC from 5 Italian centers. Patients with a macroscopically incomplete initial resection or absence of detrusor muscle were subjected to ReTUR according to European Associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…They found that among those not undergoing the early second resection, only 17.5% experienced recurrence of the disease during the follow-up without evidence of upstaging. 6 These findings support that ReTUR indication should be tailored to the patient risk factors for T1 HG persistence because it is the only solid prognostic indicator. In this scenario, ReTUR might be avoided not only in Ta HG patients that underwent complete first resection with the presence of detrusor muscle in the pathological specimen as prescribed by EAU guidelines, but also in selected small solitary T1 tumors.…”
Section: Table 2 (Continued)supporting
confidence: 54%
See 2 more Smart Citations
“…They found that among those not undergoing the early second resection, only 17.5% experienced recurrence of the disease during the follow-up without evidence of upstaging. 6 These findings support that ReTUR indication should be tailored to the patient risk factors for T1 HG persistence because it is the only solid prognostic indicator. In this scenario, ReTUR might be avoided not only in Ta HG patients that underwent complete first resection with the presence of detrusor muscle in the pathological specimen as prescribed by EAU guidelines, but also in selected small solitary T1 tumors.…”
Section: Table 2 (Continued)supporting
confidence: 54%
“…They found that among those not undergoing the early second resection, only 17.5% experienced recurrence of the disease during the follow-up without evidence of upstaging. 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contieri et al in a multicenter prospective trial investigated whether second TUR could be avoided in patients with T1 NMIBC. 20 In that study, second TUR was initially avoided in 75% of the patients (n = 57) because of the complete resection and presence of detrusor muscle in the resected samples, in 67% of patients (n = 38) who had no evidence of residual tumor in urine cytology and cystoscopy leading to immediate induction of intravesical BCG therapy, and 33% of patients (n = 19) underwent second TUR because they demonstrated positive urine cytology or suspicious lesions under cystoscopy. Of the 57 patients, 10 patients had recurrence after a median followup of 11 months.…”
Section: Discussionmentioning
confidence: 99%
“…overall economic burden of NMIBC treatment and follow-up, in addition to its critical impact on the psychological health and quality of life of patients. 24 Drug costs for the MIBC group were also roughly twice the costs for the NMIBC subgroups. Similar findings have been reported in two studies of cost in NMIBC.…”
mentioning
confidence: 99%